EUFEMISME DALAM WACANA HUMOR PROGRAM OPERA VAN JAVA (OVJ) AWARD DI TRANS 7 - SURACHMI, SRI (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
The research studied on the euphemism in the program of Opera Van Java Awards 2011 based on sociolinguistic approach. This research aimed at describing the functions of the euphemism in the program and the background of using the euphemism. In accordance with sociolinguistic approach, the conditions of the variety of euphemism were settings, ends, and norms. The use of euphemism in the humor discourse of Opera Van Java Awards 2011 was inclined to reveal joking and laughing because it often showed the diverse connotation; moreover it was supported by the funny actors and actress.Keywords: euphemism, humor, sociolinguistic